Evolutionary pattern of karyotypes and meiosis in pholcid spiders (Araneae: Pholcidae): implications for reconstructing chromosome evolution of araneomorph spiders - Ávila Herrera, Ivalú M; Král, Jiří; Pastuchová, Markéta; Forman, Martin; Musilová, Jana; Kořínková, Tereza; Šťáhlavský, František; Zrzavá, Magda; Nguyen, Petr; Just, Pavel; Haddad, Charles R; Hiřman, Matyáš; et al. (BMC ecology and evolution, 2021)
BACKGROUND: Despite progress in genomic analysis of spiders, their chromosome evolution is not satisfactorily understood. Most information on spider chromosomes concerns the most diversified clade, entelegyne araneomorphs. Other clades are far less studied. Our study focused on haplogyne araneomorphs, which are remarkable for their unusual sex chromosome systems and for the co-evolution of sex chromosomes and nucleolus organizer regions (NORs); some haplogynes exhibit holokinetic chromosomes. To trace the karyotype evolution of haplogynes on the family level, we analysed the number and morphology of chromosomes, sex chromosomes, NORs, and meiosis in pholcids, which are among the most diverse haplogyne families. The evolution of spider NORs is largely unknown. RESULTS: Our study is based on an extensive set of species representing all major pholcid clades. Pholcids exhibit a low 2n and predominance of biarmed chromosomes, which are typical haplogyne features. Sex chromosomes and NOR patterns of pholcids are diversified. We revealed six sex chromosome systems in pholcids (X0, XY, X1X20, X1X2X30, X1X2Y, and X1X2X3X4Y). The number of NOR loci ranges from one to nine. In some clades, NORs are also found on sex chromosomes. CONCLUSIONS: The evolution of cytogenetic characters was largely derived from character mapping on a recently published molecular phylogeny of the family. Based on an extensive set of species and mapping of their characters, numerous conclusions regarding the karyotype evolution of pholcids and spiders can be drawn. Our results suggest frequent autosome-autosome and autosome-sex chromosome rearrangements during pholcid evolution. Such events have previously been attributed to the reproductive isolation of species. The peculiar X1X2Y system is probably ancestral for haplogynes. Chromosomes of the X1X2Y system differ considerably in their pattern of evolution. In some pholcid clades, the X1X2Y system has transformed into the X1X20 or XY systems, and subsequently into the X0 system. The X1X2X30 system of Smeringopus pallidus probably arose from the X1X20 system by an X chromosome fission. The X1X2X3X4Y system of Kambiwa probably evolved from the X1X2Y system by integration of a chromosome pair. Nucleolus organizer regions have frequently expanded on sex chromosomes, most probably by ectopic recombination. Our data suggest the involvement of sex chromosome-linked NORs in achiasmatic pairing.
Keywords: Diffuse stage; Animals; Meiosis; pavouci; karyotypizace; meióza; Karyotyping; Entelegyne; Spiders; rDNA; Inactivation; karyotyp; Rearrangement; pohlavní chromozomy; Sex Chromosomes; Karyotype; Y chromosome; Segregation; Achiasmatic pairing; zvířata; Haplogyne